Social robots, are they emotional? - Iza-Miqueleiz, Mauricio (My University, 2021)
There have been several approaches to modelling human cognition. Implementing these structures and processes finishes in reduced performance along some dimensions. We need a convergence among cognitive architectures from two points of view: (i) computational aspect, necessity to perform complex tasks in demanding contexts; (ii) implementational aspect, reflecting the exponentially increasing knowledge figure about the nature of brain processes.
Keywords: Psicología - Congresos; cognitive architectures; emotional processing